Fast Kinetic Scheme: Efficient MPI Parallelization Strategy for 3D Boltzmann Equation (Communications in Computational Physics, 2018)
In this paper we present a parallelization strategy on distributed memorysystems for the Fast Kinetic Scheme — a semi-Lagrangian scheme developed in [J.Comput. Phys., Vol. 255, 2013, pp 680-698] for solving kinetic equations. The originalalgorithm was proposed for the BGK approximation of the collision kernel. In thiswork we deal with its extension to the full Boltzmann equation in six dimensions,where the collision operator is resolved by means of fast spectral method. We presentclose to ideal scalability of the proposed algorithm on tera- and peta-scale systems.